ANALISIS PENGARUH KENAIKAN TARIF PPN 11% TERHADAP PENJUALAN PADA PT X - Veni Gerhana Putri; Agus Subandoro (LPPM Universitas Bina Bangsa, 2022)
Tax is a mandatory contribution or contribution paid by the people or taxpayers to the state that is coercive and does not receive direct compensation for the benefit of the government and the welfare of the community. There are several types of taxes in Indonesia, such as Income Tax Article 21, Income Tax Article 22, Income Tax Article 23, Income Tax Article 24, Income Tax Article 25, Income Tax Article 26, Income Tax Article 15, Income Tax Article 4 Paragraph 2, and no less popular are VAT and/or PPnBM. Around us, transactions with taxes often occur and are very close to Indonesian citizens where the tax is objective and not subjective, the tax is Value Added Tax (VAT). In this study, the research method used was descriptive quantitative. This study will discuss the problem by describing, calculating, and comparing a situation as well as explaining a situation. The results of the study indicate that an increase in the VAT rate of 11% at PT Riaputra Metalindo has a significant effect on sales of the company's products